2022
DOI: 10.7759/cureus.25716
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriologic Profile Along With Antimicrobial Susceptibility Pattern of Pediatric Pyoderma in Eastern India

Abstract: BackgroundPyogenic skin infection (pyoderma) is a bacterial infection of the skin and its appendages. Primary pyoderma is caused by the direct invasion of healthy skin, whereas secondary pyoderma originates in diseased skin as superimposed conditions, such as scabies, pediculosis, wounds, insect bites, and eczema. This study aimed to identify the clinical patterns and risk factors of pyoderma in a pediatric population and to isolate various causative bacteria and determine their susceptibility patterns. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
3
2
0
Order By: Relevance
“…Primary pyoderma was more frequent (89; 76.72%) than secondary pyoderma (27; 23.28%). The higher prevalence of primary pyoderma was also reported in a previous report, which strengthens the findings of this study [ 20 ]. The detailed history of patients revealed that the majority of patients (97; 83.62%) never visited the clinical laboratories for the pus culture and sensitivity.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Primary pyoderma was more frequent (89; 76.72%) than secondary pyoderma (27; 23.28%). The higher prevalence of primary pyoderma was also reported in a previous report, which strengthens the findings of this study [ 20 ]. The detailed history of patients revealed that the majority of patients (97; 83.62%) never visited the clinical laboratories for the pus culture and sensitivity.…”
Section: Resultssupporting
confidence: 93%
“…In the present study, S. aureus isolates exhibited decreased (23.3–53.4%) susceptibility to penicillin, cefoxitin, erythromycin, ciprofloxacin, tetracycline and trimethoprim–sulfamethoxazole ( Table 2 ). Nonetheless, all the isolates appeared susceptible to linezolid, which was in line with the findings of earlier studies [ 19 , 20 ]. Linezolid-resistant Staphylococcus isolates have not been frequently reported.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This has been related to under developed epidermal barrier in children and adolescents. A male predominance was noted, consistent with other studies [9][10] . This could be due to higher probability of occupational hazards and exposure to bacteria in males.…”
Section: Discussionsupporting
confidence: 92%